VISUALISASI NILAI PENDIDIKAN KARAKTER DALAM RELIEF CERITA HEWAN DI CANDI SOJIWAN - Ika Dewi Retno Sari (Berkala Arkeologi, 2013)
This study aims to analyze the relevance of values that exist in the relief of animal stories in Sojiwan temple with the present character education. The approach used is qualitative approach with descriptive phenomenological method. From the research it is known that the animal story selected as the fable is a story that is very popular and known by all people at various places. Here Animals are seen as a projection of human behavior and nature, so that the nature of humor within the fable could evoke willingness for introspection and retrospection. Fable in Sojiwan temple’s relief as one of Indonesian culture containing moral teachings that are still very relevant to character education for the younger generation of today. Schools and educators need to develop teaching and educational programs based on the local culture. Families and communities also need to be involved in character education for the younger generation, through habituation virtuous behavior.